Joint statement by the President of the Republic of Colombia, Álvaro Uribe Vélez and the President of the Republic of Ecuador, Lucio Gutiérrez Borbúa. - Uribe Vélez, Álvaro (2016)
The President of the Republic of Ecuador, Lucio Gutiérrez Borbúa, made a State visit to Colombia on March 16 and 17, 2004, in response to the invitation made by the President of the Republic of Colombia, Doctor Alvaro Uribe Vélez.  During the working meeting, both leaders and their respective Ministers of State held a series of working meetings in order to strengthen the traditional ties of friendship and brotherhood between the two countries, with a view to expanding integration, cooperation and the fraternal ties that have always characterized the relations between the two countries.